Diagnóstico sanitário e ambiental de empreendimento agroalimentares: um estudo da feira dos produtores rurais no município de Castanhal-PA - GALVÃO, Bráulio Veloso (2019)
This work presents the results of the research carried out from March 2018 to June 2019, on the current sanitary and environmental infrastructure conditions of the Castanhal rural farmer's fair (AFEPRUC). In this sense, the research exposes the importance of the farmer's fair for society in the search for better working conditions and increasingly healthy products that are produced by the farmers themselves and consumed by several people who frequent the place in search of satisfying their needs. a healthy environment that offers products of a certain quality. Based on these issues, this research aims to investigate the current infrastructure conditions of the enterprise with the purpose of proposing sanitary and environmental adequacy measures to improve the quality of work and life of people who use the environment, as well as providing a better condition. suitable for marketing products from farmers' farms. The methodology designed for this study was classified as exploratorydescriptive type, qualitative nature and the chosen object was the case study. With regard to investigation techniques, data collection was based on action research and its analysis was made. through content analysis, with the production of graphs, charts and tables. The results obtained in this work were divided into three stages. The first stage comprises the characterization of the demographic profile of the farmers working at AFEPRUC, being a group of people mostly female, who live in the agrovillas that are in the adjacent areas of the In the urban headquarters of the municipality of Castanhal, these people are over 40 years old, but with mostly educational level with only incomplete elementary school, the family income of most of these people is up to 01 minimum wage, which is a worrying factor. It can end up causing various social problems. The second stage presents the environmental sanitary diagnosis of the current infrastructure conditions of the enterprise where several irregularities were identified regarding the infrastructure, most of which are precarious, with inadequate floor, rusty metallic structure, very small and unorganized parking, problems of signaling, restrooms in need of renovation and poor hygiene. Regarding the form of exposure of marketed foods, it was observed that the vast majority (62%) occurred inappropriately, and their storage was improper and deficient. The third stage expresses the sanitary and environmental adequacy plan using the SWOT and 5W2H analysis tools that served as the basis for the construction and implementation of measures to mitigate the weaknesses and internal and external threats detected during the study of the enterprise.